Extracellular vesicles derived from human dental pulp stem cells promote osteogenesis of adipose-derived stem cells via the MAPK pathway. (November 2020) - Jin, Qiaoqiao; Li, Peilun; Yuan, Keyong; Zhao, Fen; Zhu, Xiaohan; Zhang, Pengfei; Huang, Zhengwei
Recent studies have shown that co-culture systems play an important role in bone tissue engineering. In this study, human dental pulp stem cells (hDPSCs) were co-cultured with human adipose-derived stem cells (hADSCs), and osteoblastic phenotypes were found to be enhanced in co-cultures compared with monocultures of hDPSCs or hADSCs. Furthermore, GW4869, an inhibitor of extracellular vesicle (EV) formation, suppressed the mineralization of co-cultured cells. Studies indicate that the therapeutic potential of DPSCs is realized through paracrine action, in which EVs play an important role. To study their role, we successfully obtained and identified hDPSC-derived extracellular vesicles (hDPSC-EVs), and further investigated their effects on hADSCs and the underlying mechanism. hADSCs were stimulated with hDPSC-EVs, which were found to promote the migration and mineralization of hADSCs. Moreover, hDPSC-EVs promoted osteogenic differentiation by enhancing the phosphorylation of ERK 1/2 and JNK in hADSCs. To investigate the specific proteins in EVs that might play a role in hADSC osteogenic differentiation, we performed proteomic analysis of hDPSC-EVs. We determined the top 30 enriched pathways, which notably included the insulin signaling pathway. The number of genes enriched in the insulin signaling pathway was the largest, in addition to the "protein processing in endoplasmic reticulum" term. The MAPK cascade is a typical downstream pathway mediating insulin signaling. To further study the effects of hDPSC-EVs on maxillofacial bone regeneration, we used hDPSC-EVs as a cell-free biomaterial in a model of mandibular defects in rats. To assess the therapeutic potential of EVs, we analyzed their proteome. Animal experiments demonstrated that hDPSC-EVs promoted the regeneration of bone defects. Overall, these results highlight the potential of hDPSC-EVs to induce lineage specific differentiation of hADSCs. The results also indicated the importance of considering hDPSC-EVs as biomimetic materials for clinical translation of treatments for oral maxillofacial defects.